Performance management of Clostridium difficile infection in hospitals – The carrot or stick approach?. (February 2016) - Fitzpatrick, Fidelma; Riordan, Mary O.
Abstract: Public and political pressure for healthcare quality indicator monitoring, specifically healthcare-associated infection (HAI) has intensified the debate regarding the merits of public reporting and target setting as policy approaches. This paper reviews the evidence for these approaches with a focus on HAI, including Clostridium difficile infection (CDI). Healthcare key performance indicators (KPIs) and associated targets have been used widely with little evaluation. While targets are associated with some HAI reductions including CDI, as their control is multi-factorial, it is likely that reductions are due to numerous, concurrent control measures. Targets may help tackle organizational-wide issues that require high level management engagement and have contributed to the increased access and influence of infection control teams. HAI public reporting has also gained traction and is mandatory in many countries despite little scientific evaluation. CDI is one of the KPIs used but there is little consensus as to the best KPI for public reporting. Countries without public reporting have also seen improvements. Using indicator-based strategies rather than evidence-based ones risk improving the KPI but not necessarily quality of care. 'Bottom-up' approaches focussing on quality improvement and innovation generated by front line staff are seen as a lever for sustainable change. Positive deviance, where the resourcefulness and problem solving abilities of staff is harnessed, enables 'bottom-up' changes with process and outcome improvements. As implementation of best practice in healthcare is dependent on behavioural and cultural change, it is most likely that a combination of 'top-down' and 'bottom-up' approaches are required for sustainable improvement. This combined approach was used to improve staff influenza vaccination rates. Regulation may initially direct the spot-light onto infection control needs but true sustainable HAI reduction will only be fostered with concurrent cultural and behavioural shifts in practice and ownership of the HAI burden across clinical, policy and management domains. It will be interesting if this approach will be increasingly used by policy makers, however, irrespective it is clear that there is a need for rigorous evaluation of our HAI policy approaches from this point forward. Highlights: Key performance indicators (KPIs) are used as policy approaches for healthcare-associated infection (HAI) reductions, including Clostridium difficile infection (CDI) with little evaluation. Many countries publically report HAI rates using indicator-based strategies rather than evidence-based ones with the associated of risk improving the KPI but not necessarily quality of care. 'Bottom-up' approaches, including positive deviance, focussing on quality improvement and innovation generated by those working at ward level are seen as a lever for sustainable change. True sustainability in HAI reduction will only be fostered with concurrent cultural and behavioural shifts in practice and ownership of the HAI burden across clinical, policy and management domains.